Acousto-optic properties of GexS100–x glasses and acousto-optic modulator on their basis - Bletskan, D. I.; Vakulchak, V. V.; Fedelesh, V. I. (Technology and design in electronic equipment, 2014)
The investigation of acousto-optic properties of GexS100–x glasses, which had shown that they are perspective lightsoundwire material for manufacturing of acousto-optic devices for controlling the laser radiation in the visible spectral region was performed. Taking into account the technological conditions for synthesis of glasses with optical quality, the two optimal compositions, Ge30S70 and Ge25S75, were proposed for fabrication of optical-acoustic modulator. These compositions possess the high optical perfection and transmission in the spectral range of 0.4 – 11 μm, the moderate optical absorption of 2 – 3 dB/cm, their acoustic quality factor ~100 times exceeds those of quartz. The construction and main parameters of the acousto-optic modulator based on Ge30S70 and Ge25S75 glasses as lightsoundwire material and the converter is a plate of lithium niobate single crystal were described. In Bragg diversion mode the modulator has the maximum bandwidth of the modulating frequencies — 10 MHz, the diffraction efficiency — 40%, the speed — near 80 nanoseconds. It is also important to note that the effective modulation is obtained with the low power (40 mW) controlled electrical signal, which facilitates a thermal mode of the modulator and allows working without the forced cooling of the modulation element.